Meaning in life and influencing factors among Chinese nurses: a multi-center cross-sectional study - Ma, Hongli; Wu, Siqi; Li, Rui; Luo, Lei; Yuan, Huirong; Gong, Youwen; Zheng, Hongling (Frontiers in Psychology, 2026)
BackgroundMeaning in life is a comprehensive understanding of the significance and aim of one's own existence. There is limited research that specifically focuses on meaning in life for nurses, whose work may expose them to substantial workloads, intricate interpersonal dynamics, frequent exposure to death, round-the-clock shifts, and workplace violence. Meaning in life can be beneficial for nurses' psychological well-being and indirectly enhance patients' quality of care. This study explored the impact of sociodemographic factors, death anxiety and attitudes toward death on the meaning in life for Chinese nurses in Sichuan Province.MethodBetween February to April 2024, a multicenter cross-sectional survey involving 1698 Chinese nurses from 60 hospitals across Sichuan Province was conducted. A self-designed sociodemographic survey, Meaning in Life Questionnaire, Templer-Death Anxiety Scale, and Frommelt Attitudes Toward Care of the Dying Scale Form B were used to collect data. A multiple linear regression model was used to identify significant variables related to meaning in life based on sociodemographic factors, death anxiety, and attitudes toward death.ResultA total of 1,388 valid questionnaires were obtained. The average score for meaning in life among Chinese nurses was 50.37 ± 9.30. Having religious beliefs, attitudes toward death, married status, senior title, secondary grade B and below hospital, and being a head nurse were statistically significant for meaning in life, and these factors explained 24.9% of the variance (F = 25.364, P < 0.001).ConclusionThe study revealed that nurses in Sichuan Province have a moderate level of meaning in life, which is influenced by their attitudes toward caring for dying, marital status, religious beliefs, title, hospital grade, and position. Administrators and regulatory bodies could leverage these personality traits to develop targeted interventions.